Decentering grades in Year 1: conceptualising Feedback First, a feasibility trial of ungrading at programme level - Kirsty Miller; Hannah Merdian; William Burkitt; Liz Mossop (Journal of Learning Development in Higher Education)
The preparation of students for an unpredictable future means higher education plays a substantial role in supporting students to develop core graduate competencies: risk-taking and learning from failure; effective collaboration and communication; critical thinking; and a love of learning. This competency development can be undermined by grading practices. Grading can also foster unhealthy competition, inducing stress and anxiety. Ungrading is often associated with decentering grades within the learning process with removal of letter/number grades to assess students’ work; instead, students are encouraged to develop mastery of skills. In previous studies, students who have been exposed to ungrading have shown increased motivation and an appetite for risk-taking and curiosity, however, its impact on mental wellbeing is not clearly established. This paper describes an initial ungrading feasibility trial, called Feedback First, at a UK university, presenting a pedagogical innovation and strategy change focused on reorienting staff and students to consider growth and development across the first-year of our degree provision. This involved pass/fail assessment, increased collaboration, and feedback focus. We will describe the process of developing the Feedback First format, outline how we gained school and institutional support for this change of practice, present our evaluation strategy, and reflect on challenges encountered in the development and implementation of this trial.